2017
DOI: 10.18632/oncotarget.15287
|View full text |Cite
|
Sign up to set email alerts
|

Impact of vascular endothelial growth factor gene-gene and gene-smoking interaction and haplotype combination on bladder cancer risk in Chinese population

Abstract: AimsTo investigate the association of single nucleotide polymorphisms (SNPs) within vascular endothelial growth factor (VEGF) gene polymorphisms, additional gene- gene and gene- smoking interactions with bladder cancer risk.ResultsBladder cancer risk was significantly higher in carriers of the rs699947- A allele within VEGF gene than those with rs699947- CC genotype (CA+ AA versus CC), adjusted OR (95%CI) = 1.70 (1.16–2.31), and higher in carriers of the rs833052- A allele of within VEGF gene than those with r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
21
0
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(23 citation statements)
references
References 32 publications
1
21
0
1
Order By: Relevance
“…Furthermore, other contrasting results were reported; Ruhi Kapahi found a significant increase of AA genotype frequency in patients with breast cancer disease with 2.87‐fold risk . Same risk associations were reported with cervical cancer, thyroid carcinoma, bladder cancer, and breast cancer risk . But it's noteworthy that others studies failed to found any significant associations with different cancer type including gastric, bladder breast, renal, and Gallbladder cancer .…”
Section: Discussionmentioning
confidence: 94%
See 2 more Smart Citations
“…Furthermore, other contrasting results were reported; Ruhi Kapahi found a significant increase of AA genotype frequency in patients with breast cancer disease with 2.87‐fold risk . Same risk associations were reported with cervical cancer, thyroid carcinoma, bladder cancer, and breast cancer risk . But it's noteworthy that others studies failed to found any significant associations with different cancer type including gastric, bladder breast, renal, and Gallbladder cancer .…”
Section: Discussionmentioning
confidence: 94%
“…Considering +936C/T SNP, it's always reported to be in weak LD with both ‐2578C/A and ‐2549I/D polymorphisms …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“… 4 Vascular endothelial growth factor is known as a lymphangiogenic growth factor and plays an important role in tumor lymphangiogenesis via activation of the VEGF receptor. 5 Present data indicate that VEGF gene polymorphisms were associated with the risk of cancers, such as bladder cancer, 6 papillary thyroid carcinoma, 7 lung cancer, 8 hepatocellular carcinoma, 9 and renal cell carcinoma. 10 The VEGF pathway also plays a prominent role in the growth and progression of human cancer, including gastric cancer.…”
Section: Introductionmentioning
confidence: 88%
“…Одним з основних факторів виживання і поширення пухлинних клітин є ангіогенез. На даний момент, накопичено безліч даних, що підтверджують участь VEGF (фактор росту ендотелію судин) і TNF (фактор некрозу пухлини), відповідальних за мітогенну активність клітин, у розвитку та прогресуванні злоякісних новоутворень і, отже, є перспективними мішенями при використанні таргетної терапії [2,3,4].…”
Section: Fedevychvit@gmailcomunclassified